Swiat krola Artura ; Maladie - Sapkowski, Andrzej (Warszawa : SuperNOWA, 2001)
An essay on King Arthur, plus a short love story.
Keywords: Arthurian romances; Polish essays; Great Britain -- History -- To 1066.